Recognising individuals using their brain patterns - Ravi,, FVR; Palaniappan, R (2005)
In this paper, a novel method to recognise persons using their brain patterns is proposed. These brain patterns are obtained when the individuals perceive a picture. High frequency brain energy is used as features that are classified by Elman backpropagation neural network. The experimental results using 1600 brain signals from 40 individuals give average classification rate of 96.63%. This pilot investigation shows that the proposed method of recognising persons using their brain signals is worth further study.